Algae associated with coral degradation affects risk assessment in coral reef fishes. Issue 1 (December 2017) - McCormick, Mark; Barry, Randall; Allan, Bridie
Abstract Habitat degradation alters the chemical landscape through which information about community dynamics is transmitted. Olfactory information is crucial for risk assessment in aquatic organisms as predators release odours when they capture prey that lead to an alarm response in conspecific prey. Recent studies show some coral reef fishes are unable to use alarm odours when surrounded by dead-degraded coral. Our study examines the spatial and temporal dynamics of this alarm odour-nullifying effect, and which substratum types may be responsible. Field experiments showed that settlement-stage damselfish were not able to detect alarm odours within 2 m downcurrent of degraded coral, and that the antipredator response was re-established 20–40 min after transferral to live coral. Laboratory experiments indicate that the chemicals from common components of the degraded habitats, the cyanobacteria, Okeania sp., and diatom, Pseudo-nitzschia sp.prevented an alarm odour response. The same nullifying effect was found for the common red algae, Galaxauria robusta, suggesting that the problem is of a broader nature than previously realised. Those fish species best able to compensate for a lack of olfactory risk information at key times will be those potentially most resilient to the effects of coral degradation that operate through this mechanism.